(3GdMeGjI GdbGfhfjI ddCWaGd CKfGA GdfRGYGJ GdOGNdjI ai Xd CMcGe GdbGfhf GdOhdi GdEfSGfi (B/ s - (3YHjQ YHOGdYRjR GdHQjes; (3eajO eMehO TgGHs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3Ef MeGjI GdCWaGd ai GdfRGYGJ GdeSdMI ZjQ GdOhdjI(B: (3CUHMJ bVjI OhdjI JTZd GdeLJeY GdOhdi(B: (3h bO CUHM ef GdeSJbQ ai hGbY GdJYGed GdOhdj VQhQI MeGjI GdCWaGd ef NWQ GdfRGYGJ GdeSdMI(B: (3h YOe GSJgOGage Ch JYQjVge dCjI CYeGd YScQjI ceOfjjf Ch efY JLfjOge ShGA ai Uaha GdbhGJ GdeSdMI GdQSejI Ch GdedjTjGJ GdeSdMI ai GdfRGY GdeSdM ZjQ GdOhdi(B: (3h JefM bhGYO GdbGfhf GdOhdi GdEfSGfi ddCWaGd MeGjI bGfhfjI aYfO fThH Ci fRGY eSdM jSJajO GdCWaGd ef GdMeGjI GdYGeI GdeefhMI ddCTNGU GdeOfjjf(B: (3h HfGA Ydjg(B: (3Jcad dge GdeYGedI GdEfSGfjI(B: (3h JLfHge h jdGJ GdeYGQc h eG jfLe YfgG ef CPi LSOi h eYfhi(B: (3h JTed GdMaGX Ydi MjGJge h MjGI CSQge ceOfjjf(B: (3aJWHb Ydjge bhGYO GdbGfhf GdOhdi GdEfSGfi(B: (3ceG jSJajO GdCWaGd ef GdMeGjI GdNGUI HUaJge CWaGd jMJGLhf ddMeGjI HTcd NGU CKfGA GdfRGYGJ GdeSdMI(B: (3Ydh Ydi GdMeGjI GdJi jMUdhG YdjgG ef bGfhf Mbhb GdEfSGf h GdPi hVY GdcKjQ ef GdGJaGbjGJ h GdHQhJchdGJ dMeGjJge YHQ GdGee GdeJMOI(B: (3HGdGVGaI Edi EfTGA GdeMceI GdLfGFjI GdOhdjI deMGceI eLQei GdMQH h GYJHGQ GdGYJOGA Ydi GdeOfjjf ai GdfRGY GdeSdM ZjQ GdOhdi LQjeI MQH(B: (3h CjVG gfGdc GdcKjQ ef GdeDSSGJ GdOhdjI JYed ai GdejOGf dMeGjJge h Ydi QCSgG GddLfI GdOhdjI ddUdjH GdCMeQ h GdeahVjI GdSGejI dThDf GddGLFjf h GdjhfSja(B: (3h gPG LejYI eG Sha YedJ GdOQGSI GdYdejI Ydi HMKgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B233-257s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3GdCWaGds; (3GdfRGYGJ GdeSdMI GdOGNdjIs; (3MeGjI GdCWaGds; (3GdGYeGd GdYOGFjIs; (3GdJTQO GdbSQjs; (3GdJLfjOs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs